Implementation of a Value Added Tax (VAT) Policy on Online Commercial Transaction - Hernando, Redo Alpha; Veronika (Moneta : Journal of Economics and Finance, 2023)
This study aims to analyze how the implementation of the Value Added Tax policy for e-commerce transactions in Bekasi City, as well as to analyze the obstacles and efforts related to the implementation of this Value Added Tax policy. The data analysis method in this paper uses a qualitative approach with the specificity of descriptive theory used to support the successful implementation of Georges Charles Edward III's theory which consists of 4 indicators, (1) Communication, (2) Resources, (3) Disposition, (4) Bureaucratic Structure. There are obstacles in the implementation of the Value Added Tax policy on e-commerce transactions in Bekasi. The address of the Taxpayer is invalid, the Taxpayer who has moved address but the NPWP has not been changed, the letter from the Tax Service Office does not reach the Taxpayer, and the lack of understanding of taxation . The results of this study was that there was an obligation to pay Value Added Tax on e-commerce transactions, because basically an e-commerce transaction is not different from convetional transaction only there is distinguishing trade mechanism. So there is necessary adtments to several parties and co-operation.